2006
DOI: 10.1111/j.1442-2050.2006.00560.x
|View full text |Cite
|
Sign up to set email alerts
|

Difference in expression level and localization of DNA polymerase beta among human esophageal cancer focus, adjacent and corresponding normal tissues

Abstract: The aim of this paper was to study the expression level and localization of DNA polymerase beta (polbeta) and the difference in those among the human esophageal cancer focus, cancer adjacent and corresponding normal esophageal tissues. These three kinds of tissues were collected from surgically resected tissues in 17 patients with esophageal carcinoma in Linzhou, China. Each of a total of 51 tissue pieces was divided into two aliquots: one aliquot for detection of polbeta expression by in situ hybridization an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 13 publications
(14 reference statements)
0
11
0
Order By: Relevance
“…Previous studies have shown that pol b is up-regulated in ovarian, prostate, breast, and colon cancer tissues compared to adjacent normal tissues [9][10][11]. Moreover, pol b overexpression has been detected in esophageal carcinoma by in situ hybridization and immunohistochemistry [12]. pol b overexpression in cancer cells has been shown to be regulated at post-transcriptional level by HCLS1-associated protein X-1 (HAX-1), because the 3 0 UTR of the pol b mRNA contains three stem-loop structures that modulates gene expression [13].…”
Section: Introductionmentioning
confidence: 95%
“…Previous studies have shown that pol b is up-regulated in ovarian, prostate, breast, and colon cancer tissues compared to adjacent normal tissues [9][10][11]. Moreover, pol b overexpression has been detected in esophageal carcinoma by in situ hybridization and immunohistochemistry [12]. pol b overexpression in cancer cells has been shown to be regulated at post-transcriptional level by HCLS1-associated protein X-1 (HAX-1), because the 3 0 UTR of the pol b mRNA contains three stem-loop structures that modulates gene expression [13].…”
Section: Introductionmentioning
confidence: 95%
“…Srivastava et al [9] found elevated levels of POLB expression in breast, colon and prostate cancers, and speculated that the more advanced tumors may have increased amounts of damaged DNA requiring repair by the higher levels of POLB. Dong et al [10] examined expression of POLB in surgically resected specimens in 17 patients with esophageal cancer, and found that POLB expression in tumor tissue was higher than in the corresponding normal tissue. At present, there is little information regarding POLB expression and its clinicopathologic significance in CRC.…”
Section: Introductionmentioning
confidence: 98%
“…They found that the major BER DNA polymerase, pol, was overexpressed in approximately one-third of all tumors sampled and pol was most frequently overexpressed in cancers in vivo of uterus, ovary, prostate and stomach. Our group has carried out series of researches focused on expression of DNA pol in esophageal cancer, and one of our findings is the high expression of pol in esophageal tumors, which correlates to drug-resistance of this malignancy [19][20][21][22]. In this research, we analyzed the clinical and pathological significance of pol as well as its correlation to survival of the patients, through testing its expression in both esophageal tumors and the matched normal tissues adjacent to tumor.…”
Section: Discussionmentioning
confidence: 99%